The Deployment of K-Pop in Asian Market through the Implementation of Cross-Country Business Contracts by the Korean Entertainment Company - Alifia Saraswati; Yusri Abdillah; Cacik Rut Damayanti (JURNAL ILMU SOSIAL, 2023)
Recently, the emergence of a popular commodification in the form of South Korean music, known as K-Pop, has the potential to attract youthful generations in a number of Asian nations. The massive deployment of K-Pop has become public attention on how music with uncommon language could reach many people outside South Korea. One of the entertainment companies considered responsible for the phenomenon is SM Entertainment. This company is considered one of the largest in South Korea. Thanks to its business strategy capable of deploying commodification called K-Pop could enter many Asian countries, with the local company from the target market. This research aims to analyze the business contracts between SM Entertainment and the affiliation companies to create business collaboration in the form of entry mode toward different Asian countries and to evaluate SM Entertainment's success in deploying their K-Pop's commodification in Asia. This research applied the theory of Cultural Technology, Entry Mode and Cross-Country Business Contracts with a qualitative descriptive method. The results showed that implementing cross-country business contracts is doing a number in K-Pop’s expansion across Asia by modifying the business contracts suitable for the SM Entertainment and the target market to enter the Asian Market. This research also shows  that K-Pop's expansion in the Asian Market is a successful movement since K-Pop’s commodification reached and influenced many people to consume it, especially from SM Entertainment. Nonetheless, SM Entertainment is expected in entertainment if they are eager to make this K-Pop's commodification accepted generally and not just as one- time phenomenon.